Erythromelanosis Follicularis Faciei: A Case Report and Review of the Literature - Khalid Al Hawsawi; Ohood Aljuhani; Ghassan Niaz; Haneen Fallatah; Abrar Alhawsawi (Karger Publishers, 2015)
Erythromelanosis follicularis faciei is a rare sporadic condition of unknown etiology characterized by reddish-brownish patches and follicular papules that appear commonly on the face and rarely on the neck. Herein, we report a 16-year-old male who had asymptomatic facial skin lesions since early childhood. His family history revealed a similar case in his younger brother. His parents are not consanguineous. Skin examination revealed diffuse nonscaly brownish patches with erythematous background and multiple skin-colored, hypopigmented follicular papules on both cheeks. A summary of previous reports of erythromelanosis follicularis faciei in the literature is presented in this report.